On the security of a lightweight authentication and encryption scheme for mobile ad hoc network. Issue 17 (10th February 2015) - Yap, Wun‐She; Liu, Joseph K.; Tan, Syh‐Yuan; Goi, Bok‐Min
Abstract In 2011, Eissa, Razak and Ngadi proposed a lightweight authentication and encryption scheme to enhance the performance for mobile ad hoc network in Wireless Network, Vol. 17, No. 4, 2011. The main building block of such scheme is an identity‐based encryption scheme. The scheme was proven secure in the random oracle model assuming the computational Diffie–Hellman assumption is hard. In this paper, we show that the proposed scheme is not even secure against chosen plaintext attack, which is the lowest acceptable level of security. In addition, we demonstrate the RSA parameter suggested by Eissa et al. to yield a better network performance is not appropriate under a wrong security assumption that each mobile node is totally trusted. Such short RSA parameter leads to a key recovery attack. Copyright © 2015 John Wiley & Sons, Ltd.